(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2025)
This essay examines the form and function of militant literary criticism within the Italian twentieth-century cultural context, questioning both the factors that enabled its central role and the reasons behind its gradual disappearance. Through a historical and critical reconstruction of emblematic controversies—such as those surrounding Gli indifferenti, Il Gattopardo, and La storia—the author demonstrates how militant reviewing functioned as an ideological intervention and a means of cultural positioning, embedded in a dynamic exchange with the literary society of the time. The essay identifies three essential conditions for the existence of this critical mode: a relatively closed yet recognizable intellectual circuit, a non-specialist middle readership, and a strong extraliterary anchoring. Militant reviewing is thus defined by its paradoxical nature—both ephemeral and universal—capable of linking the particular to a broader ideological framework. In conclusion, the author considers what remains of this tradition today and identifies, in certain online literary platforms, the potential for a renewed critical militancy suited to the media landscape of the twenty-first century.